Effect of authentic leadership on work readiness: the mediating role of nurses' agility - Ahmed Farghaly Tawfik; Shimaa Abd El-fattah Mahgoub (BMC, 2024)
Abstract Background The dynamic and demanding nature of healthcare environments necessitates that nurses not only possess clinical proficiency but also exhibit high levels of work readiness to adapt swiftly to changes. Authentic leadership has been recognized as a critical factor influencing various organizational outcomes. Aim Investigating the mediating role of nurses' agility in the relation between authentic leadership and nurses' work readiness. Design and method A correlational analytical research design was utilized following STROBE guidelines, and data were collected from 249 nurses at a hospital affiliated with Beni-Suef University, Egypt. Instruments included authentic leadership Questionnaire, work readiness scale, and workforce agility scale. Data was collected from the beginning of March to the end of April 2024. Results The findings indicate that authentic leadership was notably strong regarding morality/ethics dimension (mean score: 15.81), and nurses demonstrated relatively high agility levels, particularly in proactivity (mean score: 29.16). Organizational acumen scored highest in work readiness dimensions (mean score: 53.94). Nurses' overall scores for study variables ranged from 72 to 80% of the maximum, with agility scoring highest (mean score: 85.77). Significant positive correlations were found between variables, especially between nurses' agility and authentic leadership (r = 0.362). Conclusion Path analysis reveals nurses' agility as a paramount mediator between authentic leadership and nurses' work readiness, indicating its vital role in transmitting the positive effects of authentic leadership. Practical implications include establishing authentic leadership programs that foster nurses' agility especially proactive behaviors. That in turn improve nurses' readiness for various work responsibilities.